(abstract) Timing and Extent of Wurm-Wisconsinan Deglaciation and Subsequent Rebound in Antarctica - Ivins, Eric I.; James, Thomas S. (2004)
Recent information from glacio-geomorphologists, when coupled to new glacio-sedimentary dating of the grounded ice sheet in the Ross Embayment at the last glacial maximum, leads to the conclusion that global geophysical models might require some revision. We investigate such new models and the possible implications for observable geodetic signatures, such as rebound-driven temporal variations in the Earth's low-order gravity field and in vertical crustal motions.